High-performance liquid chromatography with sequential injection for online precolumn derivatization of some heavy metals - Rodjana Burakham (2018)
HPLC was coupled with sequential injection (SI) for simultaneous analyses of some heavy metals, including Co(II), Ni(II), Cu(II), and Fe(II). 2-(5-Nitro-2-pyridylazo)-5-[N-propyl-N-(3-sulfopropyl)amino]phenol (nitro-PAPS) was employed as a derivatizing reagent for sensitive spectrophotometric detection by online precolumn derivatization. The SI system offers an automated handling of sample and reagent, online precolumn derivatization, and propulsion of derivatives to the HPLC injection loop. The metal-nitro-PAPS complexes were separated on a C18-μBondapak column (3.9 × 300 mm2). Using the proposed SI-HPLC system, determination of four metal ions by means of nitro-PAPS complexes was achieved within 13 min in which the parallel of derivatization and separation were processed at the same time. Linear calibration graphs were obtained in the ranges of 0.005-0.250 mg/L for Cu(II), 0.007-1.000 mg/L for Co(II), 0.005-0.075 mg/L for Ni(II), and 0.005-0.100 mg/L for Fe(II). The system provides means for automation with good precision and minimizing error in solution handling with the RSD of less than 6%. The detection limits obtained were 2 μg/L for Cu(II) and Co(II), and 1 μg/L for Ni(II) and Fe(II). The method was successfully applied for the determination of metal ions in various samples, including milk powder for infant, mineral supplements, local wines, and drinking water. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.